2017
DOI: 10.1261/rna.061192.117
|View full text |Cite
|
Sign up to set email alerts
|

Improved microRNA suppression by WPRE-linked tough decoy microRNA sponges

Abstract: Our genes are post-transcriptionally regulated by microRNAs (miRNAs) inducing translational suppression and degradation of targeted mRNAs. Strategies to inhibit miRNAs in a spatiotemporal manner in a desired cell type or tissue, or at a desired developmental stage, can be crucial for understanding miRNA function and for pushing forward miRNA suppression as a feasible rationale for genetic treatment of disease. For such purposes, RNA polymerase II (RNA Pol II)-transcribed tough decoy (TuD) miRNA inhibitors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…Third-generation lentiviral vectors were produced in HEK293T cells as previously described 34 . One day before transfection, cells were seeded in 10cm dishes at a density of 4 × 10 6 cells/dish.…”
Section: Lentiviral Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third-generation lentiviral vectors were produced in HEK293T cells as previously described 34 . One day before transfection, cells were seeded in 10cm dishes at a density of 4 × 10 6 cells/dish.…”
Section: Lentiviral Productionmentioning
confidence: 99%
“…All lentiviral preparations were made in at least triplicates and pooled before determination of viral titers. To determine viral titers of lentiviral preparations, flow cytometric measurements of EGFP expression were used as previously described 34 . One day prior to transduction, L-AN-5 cells were seeded at a density of 5 x 10 5 cells/well in 12-well plates.…”
Section: Lentiviral Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the miRNA suppression potential of the TuD hairpin, Hollensen et al (2017) inserted an RNA element, (Woodchuck hepatitis virus [WHV] post-transcriptional regulatory element [PRE], WPRE) upstream of the TuD hairpin. The WPRE RNA element has been shown to enhance gene expression in vitro and in vivo .…”
Section: Future Developments For Mirna-targeting Therapeutics – New Tmentioning
confidence: 99%
“…TuDs are exported out of the nucleus to the cytoplasm via Exportin 5, where they specifically and potently interfere with miRNA activity [23]. Studies have also shown that RNA polymerase II promoters can be used to efficiently express TuD inhibitors within the cell [24,25]. It has been shown that adeno-associated virus-delivered TuDs induced long-term miRNA inhibition in mice [27,28].…”
Section: Introductionmentioning
confidence: 99%